SINGLE ECONOMIC ENTITY: Kajian Hukum Persaingan Usaha di Indonesia - Silalahi, Udin (Fakultas Syariah, 2018)
Single economic entity doctrine has just been applied in Indonesia. KPPU applied this doctrine in the Temasek case. This application becomes controversial among law practitioners, exactly between lawyers and KPPU. Single economic entity doctrine has been well-known in the terminology of competition business law meanwhile some law practitioners argued that this doctrine is not common yet in Indonesia. This article discusses and elaborates whether the competition business law in Indonesia has been regulated and how KPPU applies the aforementioned doctrine based on the competition business law in Indonesia. This article is normative using library research. There are three approaches used in the article; they are the act, the case, and the conceptual approaches. The result shows that single economic doctrine is implicitly regulated in the Act No. 5 Year 1999. KPPU has applied the act and decided that Temasek Group contravened the Article 27, the Act no. 5 Year 1999 about share cross ownership.